Performance-Based Management and Its Role in Enhancing Organizational Efficiency - Rafi Farizki; Rani Santika (Cakrawala Repositori IMWI)
Performance-based management has been widely adopted as a managerial approach to enhance organizational efficiency and accountability in increasingly complex and competitive environments. Many organizations continue to experience inefficiencies despite the formal implementation of performance-based management systems, indicating a gap between managerial intentions and actual operational outcomes. This study aims to examine the role of performance-based management in improving organizational efficiency by analyzing its overall effect and the relative contribution of its key dimensions, namely performance planning, performance monitoring, performance evaluation, and performance feedback. The study employs a quantitative explanatory research design, with data collected through a structured survey administered to managerial-level employees involved in the implementation and evaluation of performance-based management practices. The data were analyzed using descriptive and inferential statistical techniques to assess the relationship between performance-based management and organizational efficiency. The findings indicate that performance-based management has a positive and statistically significant effect on organizational efficiency. Performance planning and performance monitoring emerge as the strongest contributors, highlighting the importance of proactive managerial practices, while performance evaluation and feedback exhibit weaker effects, suggesting that their impact depends on the effective use of performance information in managerial decision-making. This study contributes to the performance management literature by offering an integrative organizational-level perspective and provides practical insights for managers seeking to enhance efficiency through effective performance-based management implementation.